No histology for diminutive duodenal neuroendocrine tumors: Is it safe? - Walter, Thomas (Endoscopy International Open, 2019)
For the management of diminutive duodenal neuroendocrine tumors (d-NETs), Harshit et al. have proposed – in the work accompanying this editorial – an interesting approach, the endoscopic banding without resection (BWR) technique. Given the risks associated with classic endoscopic resections and surgical procedures, and the likely favorable natural history of diminutive d-NETs, BWR may be an option for these selected patients with a very low risk of LN + and recurrence. However, a close follow-up (endoscopic, EUS and thoraco-abdominal CT scan) is then required to guarantee the safety of this policy.